2017
DOI: 10.1521/aeap.2017.29.1.38
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Prevention Opportunities With GPS-Based Social and Sexual Networking Applications for Men Who Have Sex With Men

Abstract: The goal of this study was to gain insight on the sexual health needs of men who have sex with men (MSM) who use GPS-based social and sexual networking mobile applications (apps) and the future utility of app-based interventions. A health educator promoted HIV-testing resources in four popular apps used by MSM. Content analysis was used to identify salient themes that emerged from the conversations. Four major themes were identified: (1) soliciting sexual encounters, (2) relationship building, (3) HIVand STI-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Given the now-normative nature of hookup apps among adolescent and adult MSM, implementing stricter policies is likely to be ineffective in preventing AMSM’s access to these apps. Thus, future studies should also examine the potential role of hookup apps as a context for HIV prevention and testing among AMSM 41 and the education needed for AMSM to navigate such apps safely. To the former, MSM-apps could be a forum through which to educate young users about HIV risk behaviors and sexual health responsibilities (e.g., condom use, PrEP uptake and adherence, serostatus assumptions).…”
Section: Discussionmentioning
confidence: 99%
“…Given the now-normative nature of hookup apps among adolescent and adult MSM, implementing stricter policies is likely to be ineffective in preventing AMSM’s access to these apps. Thus, future studies should also examine the potential role of hookup apps as a context for HIV prevention and testing among AMSM 41 and the education needed for AMSM to navigate such apps safely. To the former, MSM-apps could be a forum through which to educate young users about HIV risk behaviors and sexual health responsibilities (e.g., condom use, PrEP uptake and adherence, serostatus assumptions).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research demonstrates that social networking apps are acceptable and feasible platforms to promote HIV/STI testing among MSM. [32][33][34][35] Blued is the largest social networking app for MSM in China, registering 40 million users in 2019. In addition to online dating and livestreaming services, Blued provides its users with HIV-prevention services and has affiliated HIV testing sites where men can be locally examined.…”
Section: Social Enterprisementioning
confidence: 99%
“…We do not want to perpetuate a paternalistic approach to public health and medicine in which academic researchers are assumed to have the answers and communities have the problems. As examples, our CyBER (Rhodes, McCoy, et al, 2016; Rhodes et al, 2011), MAP’T (Jenkins Hall et al, 2017; Sun, Stowers, Miller, Bachmann, & Rhodes, 2015), and weCare (Tanner et al, 2016) interventions (Table 1) harness existing social media to promote HIV and STI prevention, screening, and treatment. While some have suggested that social media platforms, including online sites and mobile applications (“apps”) that facilitate social and sexual networking (e.g., Adam4Adam, Grindr, Growlr, Jackd, and Scruff), may be contributing to increased rates of HIV and STIs, we see these settings as community assets.…”
Section: Community-engaged Research Partnershipmentioning
confidence: 99%